2017
DOI: 10.1097/qad.0000000000001675
|View full text |Cite
|
Sign up to set email alerts
|

Switching from a ritonavir-boosted protease inhibitor to a dolutegravir-based regimen for maintenance of HIV viral suppression in patients with high cardiovascular risk

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 51 publications
5
51
0
2
Order By: Relevance
“…Virological suppression was maintained in 92.1% of subjects, and viraemia was suppressed in 95.3% of patients at the last visit. These rates were similar to those reported in virologically suppressed adults enrolled in the European AIDS Treatment Network (NEAT) 022 trial, in which 93.1% of individuals switching from a ritonavir‐boosted PI to a dolutegravir‐based regimen maintained virological suppression at week 48 . Similarly, previous paediatric cohort studies, involving mainly adolescents and youths, reported high rates of sustained virological success among treatment‐experienced paediatric and young adult patients with viral suppression at dolutegravir initiation .…”
Section: Discussionsupporting
confidence: 83%
“…Virological suppression was maintained in 92.1% of subjects, and viraemia was suppressed in 95.3% of patients at the last visit. These rates were similar to those reported in virologically suppressed adults enrolled in the European AIDS Treatment Network (NEAT) 022 trial, in which 93.1% of individuals switching from a ritonavir‐boosted PI to a dolutegravir‐based regimen maintained virological suppression at week 48 . Similarly, previous paediatric cohort studies, involving mainly adolescents and youths, reported high rates of sustained virological success among treatment‐experienced paediatric and young adult patients with viral suppression at dolutegravir initiation .…”
Section: Discussionsupporting
confidence: 83%
“…In the SWORD‐1 and SWORD‐2 studies that randomized virally suppressed participants to DTG‐rilpivirine or continuing on current ART, 19% of the former group reported drug‐related AEs compared to 2% in the latter group . Another randomized trial observed AEs in 12.8% of people who switched to DTG versus 7.2% in those who maintained a protease inhibitor regimen .…”
Section: Discussionmentioning
confidence: 99%
“…Eligible participants were randomly assigned (1:1) to either switch to DTG 50mg/day plus the same two NtRTIs (DTG-I group) or to continue with the same triple therapy regimen including a PI/r for first 48 weeks [14] after which all patients remaining on a PI/r were switched to DTG and followed up to 96 weeks (DTG-D group) . We assigned patients to treatment groups by computer-generated permuted blocks of four and stratified by country.…”
Section: Randomization and Maskingmentioning
confidence: 99%
“…We performed a randomized, non-inferiority, 96 weeks, strategic trial to compare the efficacy, and impact on lipid parameters of immediate switching to DTG (DTG-I group) to that of remaining on a PI/r regimen for first 48 weeks [14] and then a deferred switching to DTG (DTG-D group) in a population with potential high CVD risk.…”
Section: Introductionmentioning
confidence: 99%